STAND FOR TEMPERATURE SURFACE EVALUATION OF FRAGMENTS OF NATURAL ENVIRONMENTS AND ITS IMITATORS - V. V. Lobunov; A. I. Kuharenko; T. V. Borbotko; L. M. Lynkov (Приборы и методы измерений, 2016)
Research in the field of development of natural environments imitators that used for thermal cloaking of military machinery always connected with high material costs due to big sizes of cloaking objects. In this way we decided to create laboratory stand and methodic for obtaining data about temperature surface of fragments of natural environments and its imitators affected by the electromagnetic radiation of the optical wavelength range. We proposed to use a thermal imaging camera instead of the traditionally used spectrophotometric equipment for obtaining spectral characteristics of the objects under study affected by the optical radiation. This method allows us to evaluate the surface temperature of the object at different angles of lighting and viewing. Obtained data allows us to estimate the degree to which the imitator corresponds to a natural environment by the temperature and it’s dynamic of change.The construction of the stand allows to select angles of source of radiation and thermal detector in range 25–75 degrees from normal to the surface of object under study. The source of radiation consists of halogen lamps of MR16 type. The number of selected lamps and its power were chosen taking into account of imitation of intensity of sun radiation.The thermal camera MobIR M4 was used as infrared detecting unit in the range of 8–12 μm. This device has a matrix with a resolution of 160 × 120 pixels and its optical field of view, both vertically and horizontally is 25 to 19 degrees. Special remotely controlled device was created to automate the process of obtaining thermal images. Proposed methodic of measuring surface temperature of objects under study consists in obtaining thermal images at equal time intervals, their analysis using special software and plotting graphs. Thus we can use the developed laboratory stand and the methodic not only for temperature surface evaluation of fragments of natural environments but for its imitators.